Microglial annexin A3 downregulation alleviates bone cancer-induced pain through inhibiting the Hif-1α/vascular endothelial growth factor signaling pathway. Issue 12 (December 2020) - Zhang, Zengli; Deng, Meiling; Huang, Jiangju; Wu, Jing; Li, Zhengyiqi; Xing, Manyu; Wang, Jian; Guo, Qulian; Zou, Wangyuan
Abstract : Abstract: Bone cancer-induced pain (BCP) is a challenging clinical problem because traditional therapies are often only partially effective. Annexin A3 (ANXA3) is highly expressed in microglia in the spinal cord, and its expression is upregulated during BCP. However, the roles of microglial ANXA3 in the development and maintenance of BCP and the underlying molecular mechanisms remain unclear. This study was performed on male mice using a metastatic lung BCP model. Adeno-associated virus shANXA3 (AAV-shANXA3) was injected intrathecally 14 days before and 7 days after bone cancer induction, and relevant pain behaviors were assessed by measuring the paw withdrawal mechanical threshold, paw withdrawal thermal latency, and spontaneous hind limb lifting. ANXA3 protein expression was downregulated in microglial N9 cells by lentiviral transfection (LV-shANXA3). ANXA3, hypoxia-inducible factor-1α (Hif-1α), vascular endothelial growth factor (VEGF) expression levels, and Hif-1α transactivation activity regulated by ANXA3 were measured. As a result, ANXA3 was expressed in microglia, and its expression significantly increased during BCP. ANXA3 knockdown reversed pain behaviors but did not prevent pain development. Moreover, ANXA3 knockdown significantly reduced Hif-1α and VEGF expression levels in vitro and in vivo. And overexpression of Hif-1α or VEGF blocked the effects of AAV-shANXA3 on BCP. ANXA3 knockdown in N9 cells significantly decreased the p-PKC protein expression in the cocultured neurons. Finally, ANXA3 overexpression significantly increased Hif-1α transactivation activity in 293T cells. Therefore, microglial ANXA3 downregulation alleviates BCP by inhibiting the Hif-1α/VEGF signaling pathway, which indicates that ANXA3 may be a potential target for the treatment of BCP. Abstract : Supplemental Digital Content is Available in the Text.The microglial ANXA3 plays a key role in the maintenance of bone cancer-induced pain and ANXA3 downregulation alleviates bone cancer-induced pain by inhibiting the Hif-1α/vascular endothelial growth factor signaling pathway.